2019
DOI: 10.1186/s40645-019-0290-1
|View full text |Cite
|
Sign up to set email alerts
|

Scaling land-surface variables for landslide detection

Abstract: As geomorphological processes operate at various spatial scales, their morphological expressions, i.e., land-surface variables (LSVs) should be scaled accordingly. Most approaches on landslide susceptibility modeling and landslide detection have been performed based on arbitrarily scaled LSVs. We propose a methodology to improve automated landslide detection by fitting each LSV to its optimal scale. We test our approach on two landslide inventories, with different landslide morphology. First, we derive seven L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Additional points of view state that different land-surface factors also have different optimal scales, and that the applied modelling technique may also influence this parameterization. Therefore, multiscale approaches are recommended for better performance in complex terrain settings (Catani et al 2013aSîrbu et al 2019. This has also been corroborated by Dragićević et al (2014), who examined these types of complex and multi-scalar contexts from regional to municipal and local scales.…”
Section: Theoretical Background Key Definitionsmentioning
confidence: 73%
“…Additional points of view state that different land-surface factors also have different optimal scales, and that the applied modelling technique may also influence this parameterization. Therefore, multiscale approaches are recommended for better performance in complex terrain settings (Catani et al 2013aSîrbu et al 2019. This has also been corroborated by Dragićević et al (2014), who examined these types of complex and multi-scalar contexts from regional to municipal and local scales.…”
Section: Theoretical Background Key Definitionsmentioning
confidence: 73%
“…In the Buzău study area , there is an available database containing 577 landslide scarps, acquired in the last 40 years and compiled from different sources, such as archive data, detailed geomorphological field mapping, local authority databases, digital stereographic photo interpretation using color aerial ortho-photographs 33 , 34 . For the Shizuoka study area, we used an inventory of 371 landslide scarps, provided by the National Research Institute for Earth Science and Disaster Resilience, Japan (NIED) 35 – 37 .…”
Section: Methodsmentioning
confidence: 99%
“…For the Shizuoka study area, we used an inventory of 371 landslide scarps, provided by the National Research Institute for Earth Science and Disaster Resilience, Japan (NIED) 35 – 37 . The inventory was derived by visual interpretation of topographic discontinuities using stereo-paired aerial photographs at a 1:40,000 scale, acquired in the 1970s 33 . Both inventories lack attributes regarding landslide types.…”
Section: Methodsmentioning
confidence: 99%
“…This allowed us to preserve all landslide surface features while significantly decreasing the data volume and removing the artifacts present in the data at the original resolution. The issues connected with the suitable DEM resolution have been investigated by various scientists, many of whom reported that the finest DEM resolution is not the best choice [12,14,15,26,87]. Then, DEM derivatives (also called topographic variables or land-surface variables and DEM variables) were calculated from the DEM.…”
Section: Dem Generation and Feature Extractionmentioning
confidence: 99%
“…In certain conditions, such as densely vegetated terrain, field-based investigation is ineffective or even impossible [9]. Benefiting from an abundant collection of remote sensing (RS) data, automatic approaches have been introduced to landslide studies by various scientists [1,[3][4][5][6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Among the automatic methods, pixel-based (PBA) [4,5,14,16,19] and object-based (OBIA) [7,8,[10][11][12][13]15,20] classification methods can be distinguished.…”
Section: Introductionmentioning
confidence: 99%